Strategi Pembelajaran Terminologi Bahasa Jepang pada Pekerja Migran Indonesia di Jepang - Muhammad Ramadhan Saputra; Arianty Visiaty (Vocational College of Diponegoro University, 2026)
Vocabulary mastery is essential for language learning, particularly for understanding terminology in specific fields. Terminology refers to specialized vocabulary used to express specific concepts accurately. For Indonesian migrant workers (PMI) in Japan, mastery of workplace terminology is important for effective communication and improved productivity. To master terminology effectively, learners need appropriate vocabulary-learning strategies. This study aims to identify the types and frequencies of vocabulary-learning strategies used by PMI, especially in learning terminology. The study employed a mixed-methods approach using questionnaires and interviews. The questionnaire was adapted from the Vocabulary Learning Strategy Questionnaire (VLSQ) by Puagsang et al. (2017) and distributed to 122 PMI participants, while interviews were conducted with 9 informants. The findings show that PMI uses various strategies, including social, memory, cognitive, metacognitive, and determination strategies. The most frequently used strategy is translating Japanese vocabulary into Indonesian. The study also found that the use of vocabulary-learning strategies is influenced by PMI’s living and working environments, both of which are second-language environments. These conditions require PMI to develop a strong understanding of Japanese vocabulary and terminology, encouraging them to apply different learning strategies. In addition, continuous exposure to Japanese through workplace communication and reading activities supports their vocabulary acquisition. Therefore, translating Japanese into Indonesian becomes the strategy most commonly used by PMI.